The effect of different fatty acid sources on wound healing in rats assessed by matrix-assisted-laser-desorption-ionization mass-spectroscopy-imaging - Komprda, Tomáš; Sládek, Zbyšek; Švehlová, Veronika; Lacková, Zuzana; Guráň, Roman; Do, Tomáš; Wijacki, Jan; Buchtová, Marcela; Neuwirthová, Jana; Gál, Břetislav; Adam, Vojtěch; Zítka, Ondřej (Acta veterinaria Brno, 2019)
The objective of the present study was to compare the effects of dietary oils containing polyunsaturated fatty acids (PUFA) n-3 and n-6, respectively, on cutaneous wound healing in rats, and to demonstrate the usefulness of the matrix-assisted-laser-desorption-ionization mass spectroscopy-imaging (MALDI MSI) method in this type of experiment. Superiority of PUFA n-3 in this context was the tested hypothesis. Four groups of male Wistar rats by twelve animals each were fed a diet with added 5% of palm oil (P; control), fish oil (F), Schizochytrium microalga oil (Sch) and safflower oil (S), respectively, for eight weeks. Consequently, dorsal full-thickness cutaneous excisions were performed, and selected markers of wound healing were evaluated 18 days post excision. The median of signal intensity corresponding to an amount of collagen α-1 (III) fragment, quantified using MALDI MSI, decreased in a sequence P > F > Sch > S (P < 0.001). Using haematoxylin-eosin staining of the histological preparations, semi-quantitatively assessed epithelium height tended to decrease in the order of P > S > Sch > F; the wound extent in the sequence of P > Sch > S > F; and the sequence of the progress of neo-angiogenesis was assessed as S > P > F ≈ Sch. It was concluded that the tested hypothesis was confirmed only partially: PUFA n-3 showed better results regarding the wound extent, but were inferior in terms of epithelium height and progress of neo-angiogenesis. This was the first time MALDI MSI was successfully employed for evaluating skin wound healing in a rat model.
Keywords: hojení ran; dietní tuky; Dietary Fats; Fatty Acids, Unsaturated; dietní tuky nenasycené; nenasycené mastné kyseliny; výsledek terapie; Re-Epithelialization; zvířata; Dietary Fats, Unsaturated; Wound Healing; potkani Wistar; Rats, Wistar; spektrometrie hmotnostní - ionizace laserem za účasti matrice; Treatment Outcome; rány a poranění; Wounds and Injuries; kolagen typu I, řetězec alfa 1; reepitalizace; Animals; Spectrometry, Mass, Matrix-Assisted Laser Desorption-Ionization; Collagen Type I, alpha 1 Chain